การตรวจหาความเสียหายของสะพานโครงข้อหมุนโดยการวิเคราะห์ผลตอบสนองการสั่นไหว - อาทิตย์ อ่ำเกตุสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This study compares the techniques for damage detection of truss bridges from the analysis of dynamic properties of structures such as natural frequencies and mode shapes. A 2-D truss bridge is modeled in a computer to compute its natural frequencies and mode shapes. Three different techniques, consisting of the stiffness, flexibility and residual force vector, are employed to identify the damage status of the bridge. The efficiencies of all techniques are compared by considering the accuracy of the damage location and the damage severity. In addition, this study suggests the modification of the existing methods to improve the detection accuracy. Based on the obtained results, all 3 methods can detect the damage eventhough it has low severity if the damage is assumed to present in a sensitive member. However, the error from the flexibility method is significant and the residual force vector method can not detect the damage when the damage has high severity. In the case of an insensitivity member is assumed to be, the stiffness method requires more information on modes to be able to detect the damage, and the flexibility method can not detect the damage when the damage has low severity, while the residual force vector can accurately detect the damage using only the first mode information. The signal noise from instrument is considered, so that the natural frequencies and mode shapes ofthe bridge are assumed to have the error. The result indicates that the stiffness method can accurately detect the damage location with some error in the damage severity. Using this method, an error of mode shape has more effect on the accuracy of the damage detection than an error of frequency. While the residual force vector can accurately detect the damage severity, although some undamaged members are incorrectly detected. Finally, the damage detection method is improved by using the stiffness method to detect the damage location, and subsequently use the residual force vector method to calculate the damage severity.